2021
DOI: 10.3390/cancers13184617
|View full text |Cite
|
Sign up to set email alerts
|

Let-7i Reduces Aggressive Phenotype and Induces BRCAness in Ovarian Cancer Cells

Abstract: High-grade serous carcinoma of the ovary is a deadly gynecological cancer with poor long-term survival. Dysregulation of microRNAs has been shown to contribute to the formation of cancer stem cells (CSCs), an important part of oncogenesis and tumor progression. The let-7 family of microRNAs has previously been shown to regulate stemness and has tumor suppressive actions in a variety of cancers, including ovarian. Here, we demonstrate tumor suppressor actions of let-7i: repression of cancer cell stemness, inhib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 86 publications
(113 reference statements)
1
6
0
Order By: Relevance
“…Importantly, compared to all the other Let-7 family, Let-7i had the strongest correlation with tumoural immune pathways in the > 600 human tumours examined in this study, highlighting its utility in enhancing anti-tumour immunity in HGSC. This complements well with the previously reported role of Let-7i in sensitising cancer cells to PARPi and platinum-based therapies in HGSC [ 59 , 60 ]. Future work should focus on validating Let-7i’s impact on tumour immunity in other murine models of ovarian cancer as well as its ability to generate tumour antigen-specific immune response.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Importantly, compared to all the other Let-7 family, Let-7i had the strongest correlation with tumoural immune pathways in the > 600 human tumours examined in this study, highlighting its utility in enhancing anti-tumour immunity in HGSC. This complements well with the previously reported role of Let-7i in sensitising cancer cells to PARPi and platinum-based therapies in HGSC [ 59 , 60 ]. Future work should focus on validating Let-7i’s impact on tumour immunity in other murine models of ovarian cancer as well as its ability to generate tumour antigen-specific immune response.…”
Section: Discussionsupporting
confidence: 91%
“…Specifically, for Let-7i, previous studies have found that it reduces cancer cell proliferation and migration through downregulating ERK3 expression in head and neck cancer, as well as HGMCA1 expression in bladder cancer [ 57 , 58 ]. Specifically in ovarian cancer, Let-7i upregulation decreased stemness and self-renewal, reduced anchorage-independent growth, decreased functional phenotypes associated with metastasis and increased sensitivity to PARPi and platinum-based therapies [ 59 , 60 ]. We are the first to assess the in vivo effects of Let-7i therapeutic delivery in any tumour model to our knowledge and found Let-7i has a significant therapeutic effect on ovarian tumours.…”
Section: Discussionmentioning
confidence: 99%
“…Let-7a targets IGF-2, which is oncogenic in NSCLC tissue [25]; increased expression of NEAT1 downregulates let-7a, removing the miRNA block on IGF-2 expression, and resulting in increased NSCLC cell proliferation, migration and invasion [25]. Similarly, in epithelial ovarian cancer, let-7 also downregulates IGF-1, possibly contributing to a less aggressive phenotype [26] (Fig. 1).…”
Section: Let-7mentioning
confidence: 99%
“…LncRNA NEAT1 increases oncogenic IGF1R signaling by competing against miRNA Let-7a, which targets IGF-2 [25]. Let-7 also potentially downregulates IGF-1 [26]. LncRNA NR2F1-AS1 can also lead to IGF1R activation by sponging miR-338-3p, which downegulates IGF-1 [27].…”
Section: H19mentioning
confidence: 99%
“…Furthermore, ovarian cancer has been characterized as a largely heterogenous disease, resulting in varying effectiveness of currently available therapies 4,5 . Previously, our lab has focused on the characterization of a variety of patient-derived high-grade serous ovarian carcinoma (HGSOC) samples 6,7 . As the most aggressive subtype of ovarian cancer, the HGSOC samples indicated a large distribution of growth rate, morphology, gene and protein expression, and response to commonly used therapies, like cisplatin, a platinum-based agent that forms adducts with DNA, and olaparib, a poly (ADP-ribose) polymerase inhibitor (PARPi) 6 .…”
Section: Introductionmentioning
confidence: 99%